Hotspots and emerging trend analysis of extracorporeal membrane oxygenation complication research: A qualitative systematic review of literature - Xiaowei Dong; Yuan Li; Zejian Jin; Sheng Liu; Zengsheng Chen (Medicine in Novel Technology and Devices)
As an effective extracorporeal life support technology, ECMO is mainly used in patients with acute cardiopulmonary failure, but it can still cause related complications such as thrombosis, bleeding, infection, and cannulation problems, seriously endangering patients' lives and health. This review used bibliometric methods to retrieve a total of 2789 relevant documents from 2003 to March 2023 from the core database of Web of Science, used CiteSpace to draw a knowledge map, and conducted publication trend analysis, subject journal analysis, keyword co-occurrence analysis, cluster analysis, timeline and time zone diagram analysis, emergent keyword analysis. Quantitatively and qualitatively analyze the research hotspots of ECMO and its complications, and then predict the development trend in this field. It aims to provide clinicians, scientists, and related practitioners with an overview of the latest research related to the optimal design of ECMO systems, avoidance and mitigation of complications, and provide directions for subsequent research.